Monitoring Pollution and the Trend of Air Quality in Brick Factories in the Nahrawan Region and its Impact on Baghdad, Using Remote Sensing Data - Mouhmmed Jadem, Asmaa; Jasem, Israa Mohsin; Al-Ramahi, Fouad K. Mashee (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
One of the most significant environmental issues facing the planet today is air pollution. Due to development in industry and population density, air pollution has lately gotten worse. Like many developing nations, Iraq suffers from air pollution, particularly in its urban areas with heavy industry. Our research was carried out in Baghdad's Al-Nahrawan neighbourhood. Recently, ground surveys and remote sensing were used to study the monitoring of air pollution. In order to extract different gaseous and particle data, Earth Data source, Google Earth Engine (GEE), and Geographic Information Systems (GIS) software were all employed. The findings demonstrated that there is a significant positive connection between data collected by ground-based devices and remote sensing platforms. The brick manufacturers' operations in the region's northwest and west directions from Baghdad were plainly having an impact on the region of Al-air Nahrawan's quality. As a result, residents in the area are more likely to contract illnesses caused by pollution.